Respuesta :
Answer:
23°, 54°, 103°
Step-by-step explanation:
let the2nd angle = x
1st angle = x + 31
3rd angle = 2(x + 31) - 5 = 2x + 62 - 5 = 2x + 57
Sum the 3 angles and equate to 180
x + 31 + x + 2x + 57 = 180 , that is
4x + 88 = 180 ( subtract 88 from both sides )
4x = 92 ( divide both sides by 4 )
x = 23
Then
1st angle = x + 31 = 23 + 31 = 54°
2nd angle = x = 23°
3rd angle = 2x + 57 = 2(23) + 57 = 46 + 57 = 103°
Using the triangle sum theorem, the measures of the angles are:
Second angle = 23°
First angle = 54°
Third angle = 103°
What is the Triangle Sum Theorem?
The triangle sum theorem states that the sum of all the interior angles of a triangle equals 180 degrees.
Thus:
Let the second angle be represented as x
Measure of first angle = x + 31
Third angle = 2(x + 31) - 5 = 2x + 62 - 5 = 2x + 57
Thus:
x + x + 31 + 2x + 57 = 180 (triangle sum theorem)
Find x
4x = 180 - 88
4x = 92
x = 23
Plug in the value of x
Second angle = x = 23°
First angle = x + 31 = 23 + 31 = 54°
Third angle = 2x + 57 = 2(23) + 57 = 103°
Learn more about triangle sum theorem on:
https://brainly.com/question/7696843